2005
DOI: 10.1128/aac.49.1.388-397.2005
|View full text |Cite
|
Sign up to set email alerts
|

Hemolysis of Erythrocytes by Granulysin-Derived Peptides but Not by Granulysin

Abstract: Granulysin, a 9-kDa protein localized in human cytolytic T lymphoctyes and natural killer cell granules, is cytolytic against tumors and microbes but not against red blood cells. Synthetic peptides corresponding to the central region of granulysin recapitulate the lytic activity of the intact molecule, and some peptides cause hemolysis of red blood cells. Peptides in which cysteine residues were replaced by serine maintain their activity against microbes but lose activity against human cells, suggesting their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 41 publications
1
26
1
Order By: Relevance
“…1C). The results were in agreement with a previous observation (26). We also found the lytic effects of GNLY to human PBMC were comparable to the RBC (Fig.…”
Section: Recombinant Gnly Possesses Killing Activity Against Salmonelsupporting
confidence: 83%
“…1C). The results were in agreement with a previous observation (26). We also found the lytic effects of GNLY to human PBMC were comparable to the RBC (Fig.…”
Section: Recombinant Gnly Possesses Killing Activity Against Salmonelsupporting
confidence: 83%
“…Several studies have confirmed that the cytolytic activity of the 9-kDa GNLY occurs in the 50-100M range. 37 It has previously been reported that the 9-kDa recombinant human GNLY could induce migration of human peripheral blood monocytes and mature DCs, 32 but not Mo-iDCs or murine DCs. We For personal use only.…”
Section: Discussionmentioning
confidence: 97%
“…Indeed, although trophozoites and schizonts specifically triggered degranulation and granulysin release, their intracellular development was not impaired when cocultured with V␥9V␦2 T cells. Because the erythrocytic membrane is resistant to granulysin, 40 perforin does not seem to be sufficient to allow granulysin to pass this barrier and reach the intravacuolar parasite. Remaining protected from cytotoxic molecules within the erythrocyte for the duration of the intracellular development can be viewed as a Plasmodium evasion strategy that has not been appreciated previously.…”
Section: Discussionmentioning
confidence: 99%